From text to screen: Reading Shakespeare's Macbeth as a Sexual Tragedy with reference to the play's Indian Adaptaion Maqbool - Moran, Nilakshi; Moran, Nilakshi (International Journal of Psychosocial Rehabilitation, 2020)
Macbeth (1623) written by William Shakespeare and its Indian movie adaptation Maqbool (2004) directed by Vishal Bhardwaj call into question the sexual identity of the characters depicting both the male and female impotence. Inversion of Gender roles can be detected throughout both works which brings to question the conflicting opinions about Shakespeare's women at that time and how he has been accused of being a misogynist and the image of women in the Indian society being presented in the Indian movie questioning the sexual identity of the three witches and their parallel characters in the movie. There is a correlation in both works between the loss of sexuality and loss of humanity which brings into discussion the theme of inversion and regain of the natural order of things. The paper will further attempt to analyze how language is sexualized in the text through the use of some embedded obscene phrases and expressions especially to show the rampant sexuality presented in the movie.